2019
DOI: 10.1007/s42770-019-00119-w
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of high-throughput sequencing of bacterial communities for postmortem submersion interval estimation

Abstract: Microorganisms play vital roles in the natural decomposition of carcasses in aquatic systems. Using high-throughput sequencing techniques, we evaluated the composition and succession of microbial communities throughout the decomposition of rat carcasses in freshwater. A total of 4,428,781 high-quality 16S rRNA gene sequences and 2144 operational taxonomic units were obtained. Further analysis revealed that the microbial composition differed significantly between the epinecrotic (rat skins) and the epilithic (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 57 publications
4
9
1
Order By: Relevance
“…Corpse decay in the large-volume drinking water system signi cantly changed water chemistries was observed. CON signi cantly increased but DO slightly decreased over time, which is lined with previous researches (He et al, 2019;Xia et al, 2017). It is reported that CON is an indicator of total dissolved metal concentration in water environment (Yang et al, 2019;Zhang et al, 2019), which is likely to contribute to the variation of resistomes during carcass decomposition.…”
Section: Carcass Decay Changes Environmental Properties and Thus Affects The Resistomessupporting
confidence: 92%
“…Corpse decay in the large-volume drinking water system signi cantly changed water chemistries was observed. CON signi cantly increased but DO slightly decreased over time, which is lined with previous researches (He et al, 2019;Xia et al, 2017). It is reported that CON is an indicator of total dissolved metal concentration in water environment (Yang et al, 2019;Zhang et al, 2019), which is likely to contribute to the variation of resistomes during carcass decomposition.…”
Section: Carcass Decay Changes Environmental Properties and Thus Affects The Resistomessupporting
confidence: 92%
“…An experiment on three swine heads for the bacterial succession data across two seasons, five stages of decomposition, and bacterial communities showed site-and season-specific preponderance and colonization (Dickson et al, 2011). Proteobacteria, Firmicutes, Bacteroidetes, and Actinobacteria were found to be the predominant phyla in epinecrotic rat samples, which showed dynamic variation, with Proteobacteria decreasing while Firmicutes increasing during decomposition, the latter becoming the dominant phylum on days 5 and 6 (He et al, 2019). Furthermore, Clostridiaceae and Comamonadaceae were the most abundant families which displayed different succession patterns, as the former was abundant on days 1, 4, 5, and 6, while the latter decreased from day 4 onward.…”
Section: Supportive Evidence In Animal Surrogatesmentioning
confidence: 96%
“…Postmortem submersion interval (PMSI), which is the amount of time human remains have been partially or fully submerged in an aquatic environment, demands a different approach as the decomposition process in water bodies is slower with adipocere formation due to anaerobic environment when compared with that of a terrestrial environment due to the effect of water temperature, salinity, tides, depth, mobility of the carcass, and scavengers (Caruso, 2016;He et al, 2019). Epinecrotic community from S. scrofa carcasses revealed not only significant temporal shifts in the bacterial communities at the phyletic and generic levels with the progression of the decomposition process but also significant seasonal variation between summer and winter (Benbow et al, 2015).…”
Section: Supportive Evidence In Animal Surrogatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most biofilms formed on decayed animal and plant carcasses are heterotrophic, and the microbial community is primarily composed of bacteria and fungi ( Tank and Dodds, 2003 ; Sinsabaugh et al, 2010 ). Some researchers have investigated the succession process of the bacterial community in biofilm on submerged animal carcasses compared to microbial communities attaching to ceramic tiles ( Dickson et al, 2011 ; Benbow et al, 2015 ; He et al, 2019 ). Studies have shown that the bacterial community structure of the biofilm on the surface of the carcass in water differs in various seasons.…”
Section: Introductionmentioning
confidence: 99%